MENANGKAL PAHAM RADIKALISME MELALUI ORGANISASI ROHIS (TELAAH MEDIA REKONSTRUKSIONISME PENGARUH RADIKALISME PADA PELAJAR SMK DI SURABAYA) - Luluk Farida; Shafa Alistiana Irbathy; Almi Novita (STIT Al - Ibrohimy Bangkalan, 2023)
The Rohis (Islamic Student Activity Unit) in vocational schools (SMK) has currently become a platform for representatives from both public and private vocational schools to prevent the spread of radicalism among students in Surabaya. In this context, the role of Rohis is to accommodate the aspirations and problem-solving of each school, based on the experiences of students from different schools. This includes addressing issues from educators who sometimes influence their students to follow the path of radicalism they themselves have taken. This topic is intriguing to researchers because, based on field data and interviews with alumni who established this organization, the goal is to educate and enlighten students within the organization and their classmates. The method employed is qualitative, using interviews to analyze the gathered information. In this study, researchers found that current vocational school students in Surabaya consider Rohis as a platform for learning. This has brought researchers closer to the members of Rohis. After obtaining interview results, researchers will analyze the existing data using the theory of reconstructionism. The analysis reveals how Rohis members can think critically about issues within their respective schools and filter information or knowledge received by members or classmates.